Women as Victims of Human Trafficking (TPPO) In North Kalimantan Indonesia from Criminal Law and Islamic Law Perspectives - Irawan, Aris; wahyuni, Fitri; Suryani, Nilma; Asneliwarni, Asneliwarni (Nagari Law Review, 2025)
The criminal act of human trafficking (TPPO) is a serious crime that occurs on both national and international scales. It is a crime that is not easily detected because it is carried out in an organized and professional manner. Cases of human trafficking continue to increase every year, both globally and in Indonesia. This clearly proves that various international and national regulations have not been able to eliminate this crime. Therefore, it can be concluded that the high rate of human trafficking is not caused by a lack of regulations established by the government, but rather by the fact that the criminal penalties imposed on the perpetrators have not been effective in deterring them. Additionally, the existing regulations have not been fully effective in preventing the crime. Thus, it is necessary to compare the legal provisions on human trafficking with those found in Islamic criminal law. This research falls under normative legal research, using secondary data and analyzed deductively. Indonesia has regulated human trafficking in the Criminal Code (KUHP), specifically in Article 296, which prohibits human trafficking in the form of sexual exploitation. Similarly, Islamic criminal law prohibits human trafficking. This is based on the primary objectives of Islamic law (Maqāṣid al-Sharī ‘ah), which emphasize the importance of preserving five essential values: religion (dīn), life (nafs), intellect (‘aql), lineage (nasl), and property (māl), as stated in the Qur'an, Surah Al-Isra (17:70). Islamic law strictly forbids all forms of coercion, slavery, and sexual exploitation, as these actions violate the sanctity of human dignity.